Coordination of the Regional Disaster Management Agency in Disaster Handling : A Case Study in Karanganyar Regency - Farco Siswiyanto Raharjo; Sri Riris Sugiyarti; Ervyta Dyah Ramadany (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
This research examines the coordination efforts of the Karanganyar District Disaster Management Agency (BPBD) in managing disasters, identifying obstacles, and exploring efforts to strengthen these coordination efforts. Utilizing a qualitative approach with a case study method, the study aims to investigate the mechanisms of cross-sector coordination, communication patterns, and division of labor within BPBD. Data was gathered through in-depth interviews, observations, and document studies, and analyzed using an interactive model. The findings indicate that BPBD's coordination is relatively effective, demonstrated through unified action, a multi-channel communication system, and a clear division of labor. However, challenges remain, including the complexity of cross-sectoral coordination, differences in capacity and authority, and the pressure of emergency situations. The study concludes that improving coordination requires enhancing staff discipline, developing human resource capacity, and strengthening an integrated work system. These efforts are vital for improving the overall effectiveness of disaster management at the local level, ensuring a more efficient and comprehensive response to disasters in the future.